Effects of artificially increased activation of the gluteus medius on ipsilateral lower limb muscles force during gait - Omer Kursad Katirci; Diana Toderita; Anthony M. J. Bull (PLoS ONE, 2026)
Background Functional Electrical Stimulation is widely used in rehabilitation to improve muscle function in individuals with neurological impairments. The gluteus medius muscle plays a key role in pelvic stability and balance during gait. The purpose of this study was to simulate functional electrical stimulation using musculoskeletal modelling to examine the effects of artificially increased gluteus medius activation on the activation of other ipsilateral lower limb muscles during the stance phase of gait in healthy adults. Methods Musculoskeletal modelling simulations were conducted on gait data from 30 healthy participants to compare normal gait and gait modified by artificially increased gluteus medius activation. A static optimisation model was used to promote gluteus medius activation, replicating a functional electrical stimulation intervention. Changes in peak muscle forces, body-weight–normalised muscle impulse, force traces, peak hip joint reaction force, and hip joint reaction force traces were analysed. Results Artificially enhanced gluteus medius activation significantly (p < 0.05) affected the peak force of seven muscles, the body-weight–normalised muscle impulse of eight muscles, peak hip joint reaction force, the force traces of ten muscles, and hip joint reaction force traces during stance. Conclusions Increased gluteus medius muscle activation altered lower extremity muscle coordination through agonist–antagonist interactions, resulting in a redistribution of muscle forces that may be mechanistically associated with improved frontal-plane pelvic control and dynamic balance during walking. These findings, obtained in healthy individuals within an inverse dynamics-based musculoskeletal modelling framework, provide a mechanistic insight into how the increased contribution of the gluteus medius affects distal muscle loading patterns. Although this approach does not directly represent the phase-dependent or adaptive effects of functional electrical stimulation, the observed force distribution patterns may contribute to hypothesis generation for future studies investigating gait disorders.